PROSEDUR AUDIT ASET TETAP PADA LEMBAGA IST OLEH KANTOR AKUNTAN PUBLIK AU DAN REKAN - Indah Setia Triananda (2022)
Fixed assets are accounts that are very influential in a company or organization, so that fixed assets can be used as a tool to earn income for the company. Thus, the calculation of fixed assets in the company must be carried out correctly. To find out whether the calculation of fixed assets is correct or not, it is necessary to examine the account in accordance with audit procedures. Examination according to procedures that have been systematically prepared by an auditor with the aim of testing and checking for errors in numbers that greatly affect the correctness of balances in the company's financial statements. Tests on fixed asset accounts were carried out by the Public Accounting Firm (KAP) AU and Partners against the IST Institute, which is an organization founded by a group of people voluntarily who provides services to the general public without the aim of profiting from its activities. This report is prepared with the aim of informing how the process of auditing fixed asset accounts is carried out. These inspections are carried out in accordance with the audit program and audit procedures. In the audit program, there are several activities, such as performing analytical procedures, physically checking fixed assets, and calculating depreciation of fixed assets. From the above activities, it can be concluded that the 2021 IST Institution's fixed asset report has been presented fairly and no material misstatements were found.